2010
DOI: 10.1111/j.1365-2702.2010.03367.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication in nursing care for patients requesting euthanasia: a qualitative study

Abstract: Being the essence of nursing care for patients requesting euthanasia, nurses' communication requires support and guidance on the level of nursing education, professional guidelines and hospital context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 39 publications
1
67
0
1
Order By: Relevance
“…Evidence derived from nurses in Belgium has attested to the complexity of these conversations. (7,8) Countries considering the legalization of assisted death should carefully consider the impact of teamwork on best practices, including those having to do with communicating with patients and families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence derived from nurses in Belgium has attested to the complexity of these conversations. (7,8) Countries considering the legalization of assisted death should carefully consider the impact of teamwork on best practices, including those having to do with communicating with patients and families.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, registered nurses who do not hold a nurse practitioner credential also play important roles in MAiD. The important role of the registered nurse is also evident in studies from other countries where assisted death is legal [6][7][8][9][10][11]. For example, our synthesis of qualitative studies from Belgium, the Netherlands, and Canada of registered nurses' experiences with assisted death suggested that nurses perform a central role in negotiating initial inquiries about assisted death, that nurses provide important 'wrap-around' care for patients and family, and that participating in an assisted death was impactful for nurses and required significant moral work [12].…”
Section: The Nursing Role In Maidmentioning
confidence: 99%
“…The prevalence of this miscommunications left many physicians hesitant in their decisions to provide assistance in dying (Borgsteede et al, 2007;Snijdewind et al, 2014). Nurses also described the significance of communication in their role in the assisted dying process: explaining the importance of their role in the patient's becoming certain about the decision, advocating for the patient, and helping the patient come to terms with the decision (Denier et al, 2009(Denier et al, , 2010bDierckx de Casterlé, Verpoort, De Bal, & Gastmans, 2006;Schwarz, 2003). The nurses explained that they communicated with patients through active listening, providing information, translating jargon, consulting with the patient, providing advice, and engaging in non-euthanasia-related conversation to support patients receiving assistance in dying (Denier et al, 2009).…”
Section: Continued Title and Authors Country Purpose Methods Participmentioning
confidence: 99%
“…For example, Denier et al . (), in stating that ‘sampling aimed for diversity regarding characteristics of both participants and hospitals’, recruited on the basis of attributes rather than concepts. Most of the articles that did not specify a sampling term failed to convey a theoretically driven approach.…”
Section: Resultsmentioning
confidence: 99%